Syndicalism and the transition to communism: an international comparative analysis - Darlington, Ralph (Aldershot, 2008)
"During the first two decades of the twentieth century, amidst an extraordinary international upsurge in strike action, the ideas of revolutionary syndicalism developed into a major influence within the world wide trade union movement. Committed to destroying capitalism through direct industrial action and revolutionary trade union struggle, the movement raised fundamental questions about the need for new and democratic forms of power through which workers could collectively manage industry and society.This study provides an all-embracing comparative analysis of the dynamics and trajectory of the syndicalist movement in six specific countries: France, Spain, Italy, America, Britain and Ireland. This is achieved through an examination of the philosophy of syndicalism and the varied forms that syndicalist organisations assumed; the distinctive economic, social and political context in which they emerged; the extent to which syndicalism influenced wider politics; and the reasons for its subsequent demise.The volume also provides the first ever systematic examination of the relationship between syndicalism and communism, focusing on the ideological and political conversion to communism undertaken by some of the syndicalist movement's leading figures and the degree of synthesis between the two traditions within the new communist parties that emerged in the early 1920s. "